Pembelajaran Bahasa Arab melalui Kolaborasi Metode Questioning dan Media Kahoot - Ahmad Fadilah Khomsah; Muhammad Imron (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2020)
Learning that is conducive and fun in the industrial revolution 4.0 makes changes in learning styles in the learning process. Teachers are asked to follow an interactive digital learning process. Learning that is fun and not boring is one of the challenges for instructors and Developers of Learning Technology to innovate in learning. Questioning method (question and answer) is a method used by teachers in learning to arouse student motivation in expressing opinions in the learning process takes place. In Arabic there are four maharah that must be mastered. To master Arabic, learning media are needed that are effective, efficient and in accordance with the times so that students are interested and enthusiastic in participating in learning activities. However, many teachers are less creative in using existing media. Whereas learning media has a role as an attention drawer, curiosity and facilitates the delivery of information to students. This paper discusses the Collaboration of the Application of Questioning Methods with the Kahoot Application in Arabic Language Learning. Kahoot is one of the learning media in the form of web-based applications for making quizzes and simple games. Teachers as facilitators as well as content creators can add elements in the form of videos, images and texts and students can access them via a smartphone or personal computer.